Development of the Berry Happy Application for the Digitalization of Bedugul Culinary MSMEs Using the Scrum Approach - Ammulia Rizqie Ramadhana Pujiyanto; Putu Nadia Prameswari; Ketut Dian Suryasih; Putu Melianti Eka Maharani; Ketut Agus Seputra; Kadek Teguh Dermawan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The High strawberry production in the Bedugul area often results in surplus harvests that are not fully absorbed by the market, creating challenges for local farmers and strawberry-based culinary MSMEs. One of these enterprises is Berry Happy, which processes strawberries into various dessert products. However, the business still relies on manual transaction recording and has limited market reach. This study aims to design and develop a mobile-based e-commerce application to support the digitalization of business processes at Berry Happy. The application was developed using the Flutter framework and the Agile Scrum methodology, which consists of product backlog determination, sprint planning, sprint implementation, sprint review, and sprint retrospective activities. The resulting system provides features for customer registration, product browsing, shopping cart management, checkout processing, transaction history, and menu management for business owners. Functional testing was conducted using the Black Box Testing method to evaluate whether each feature operated according to the specified requirements. The testing results showed that all defined test scenarios were successfully executed and produced outputs consistent with the expected results. The developed application facilitates digital transaction management, supports product promotion through a mobile platform, and provides a more structured approach to recording business transactions. These findings indicate that the application can serve as a practical digital solution to support the operational activities of culinary MSMEs.